(untitled) (Journal of Computational Mathematics, 2021)
In this paper, we have proved that the lower bound of the number of real multiplications for computing a length 2^t real GFT(a,b) (a=± 1/2,b=0 or b=± 1/2,a=0) is 2^t+1-2t-2 and that for computing a length 2^t real GFT(a,b)(a=± 1/2, b=± 1/2) is 2^t+1-2. Practical algorithms which meet the lower bounds of multiplications are given.